Analysis of Number Sense Ability in Children with Autism Spectrum Disorder (ASD) in Solving Mathematical Problems - Barutu, Nova Kristinawati; Husna, Amalia; Winarni, Sri; Marlina, Marlina (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2022)
Children with autism have disorders that distinguish them from typical children, but children with autism can also learn in school. The learning abilities consist of cognitive, affective, and psychomotor abilities. In cognitive abilities, there are various types of abilities, one of which is the ability to number sense. This study aims to analyze the number sense ability of children with autism in solving math problems. This research belongs to the type of qualitative research that uses a descriptive approach. From the research results, the number of sense abilities in autistic children is still low and different for each autistic child, depending on their communication and concentration skills. SA1 satisfies several indicators: it determines the size of the numbers, the meaning of numbers and symbols in the set, and estimates.